Development of Hydrogen-Rich Benzoxazine Resins with Low Polymerization Temperature for Space Radiation Shielding - Iguchi, Daniela (2018)
A systematic study has been carried out to develop a material with significant protection properties from galactic cosmic radiation and solar energetic particles. The research focused on the development of hydrogen-rich benzoxazines, which are particularly effective for shielding against such radiation. Newly developed benzoxazine resin can be polymerized at 120 °C, which meets the low-temperature processing requirements for use with ultrahigh molecular weight polyethylene (UHMWPE) fiber, a hydrogen-rich composite reinforcement. This highly reactive benzoxazine resin also exhibits low viscosity and good shelf-life. The structure of the benzoxazine monomer is confirmed by proton nuclear magnetic resonance and Fourier transform infrared spectroscopy. Polymerization behavior and thermal properties are evaluated by differential scanning calorimetry and thermogravimetric analysis. Dynamic mechanical analysis is used to study chemorheological properties of the benzoxazine monomer, rheological properties of the cross-linked polybenzoxazine, and rheological properties of UHMWPE-reinforced polybenzoxazine composites. The theoretical radiation shielding capability of the composite is also evaluated using computer-based simulations.